Switching to emtricitabine, tenofovir and rilpivirine as single tablet regimen in virologically suppressed HIV‐1‐infected patients: a cohort study1. Issue 2 (15th August 2014) - Gantner, P; Reinhart, S; Partisani, M; Baldeyrou, M; Batard, M‐L; Bernard‐Henry, C; Cheneau, C; de Mautort, E; Priester, M; Fafi‐Kremer, S; Muret, P; Rey, D
<x xml:space="preserve">Abstract</x> Objectives Emtricitabine/tenofovir/rilpivirine as a single‐tablet regimen (STR) is widely used without licence in treatment‐experienced patients. The purpose of this retrospective observational study was to assess viral suppression of ART‐experienced patients switching to STR. Methods We assessed 131 pretreated patients switching to STR with HIV RNA < 400 HIV‐1 RNA copies/mL. The primary outcome measure was the proportion of patients at week 24 with HIV RNA < 40 copies/mL. Results By week 24, eight patients had stopped STR: four because of adverse events and four for other reasons. Three virological failures were observed; among these, at least one patient developed cross‐resistance to nucleoside reverse transcriptase inhibitors (NRTIs) and nonnucleoside reverse transcriptase inhibitors (NNRTIs), in particular with the E138K pattern. In intent‐to‐treat analysis, 92% of participants (120 of 131) achieved HIV RNA < 40 copies/mL. Only grade 1 to 2 adverse events were observed, mainly consisting of increased liver enzymes (n = 33). Systemic exposure to rilpivirine was above the usually observed steady‐state levels for the 18 measurements assessed. Conclusions Efficacy and tolerability are similar to those in treatment‐naïve patients.